(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Many Filipinos are going crazy about it because of its unique concept of having various side dishes, as Samgyeopsal has become popular in the Philippines. Service quality and customer satisfaction are important aspects of the business since a company’s growth is largely dependent on how well it maintains its customers through service and how well it keeps its customers satisfied. This study aims to investigate the impact of service quality on customer satisfaction for selected Samgyeopsal Restaurant in Quezon City". In terms of serving orders on the table, respondents have a minor problem when it comes to the condition of tools and equipment. The respondents have a minor problem with the instructions they give to employees. In other words, the employee did not understand the instructions well given to them by the customer. The respondents had a minor problem with the attention to their complaints. There are times that the customers do not get the attention well when they have some complaints. A recommendation for the service provider would be to focus on improving the conditions of tools and equipment to ensure that they are in good working condition and clean. The restaurant could consider implementing strategies to address any areas that were identified as opportunities for improvement, such as increased attention to customer complaints. Continue to monitor customer feedback, identify areas for improvement in their customer service processes, and maintain and improve customer satisfaction levels. Selected Samgyeopsal Restaurant should focus on improving the minor problems identified by the respondents, particularly in the areas of tools and equipment condition, instructions given to employees, and attention to customer complaints.